K Kolumbayeva S.Zh., Lovinskaya A.V., Shalakhmetova T.M., Suvorova M.A., Voronova N. The antimutagenic potential of biologically active compounds of Inula britannica L. family Compositae: Al-Farabi Kazakh national university, Almaty, Kazakhstan *Е-mail: S_kolumb@mail.ru (ҚазҰУ хабаршысы. Экология сериясы, 2017)
Cytogenetic and mutagen-modified effects of biologically active compounds (BAC) of Inula britannica L. extracts from both shoots and roots parts were investigated testing on count chromosome abnormalities of cells of barley root meristem. It was established that plant extracts in concentrations 50.0 and100.0 mg/l decrease the level of spontaneous mutagenesis in root meristem of barley.The combined exposure of seeds to methyl methanesulfonate (MMS) and extracts independentlyon treatment sequence result in statistically significant reduce of MMS-induced mutagenesis. The dataobtained testify to the presence of antimutagenic effect in studied extracts. There was revealed no differences in gene protective effect of whether aboveground or underground parts of I.britannica despite ongreater content of BAC in underground part.Key words: Inula britannica, biologically active compound, extract, mutagen, antimutagen, chromosomal aberration.